The influence of large-scale dance events on the formation of tourist attractiveness and territorial branding of cities - Dudchenko, Yuliia (Актуальні питання економічних наук, 2026)
Large-scale art events are now an element in the formation of tourist attractiveness and local branding, combining cultural, social, and economic impacts into a single mechanism for the development of urban areas. The aim of the study is to analyze the impact of dance festivals as markers of spatial identity on the formation of tourist expectations and increasing the recognition of cities. The article uses a comprehensive methodological approach, including an analysis of literary sources, a review of the practice of organizing festival events, and a systematization of the socio-economic and image effects of such events. The results of the study indicate that regularly holding dance events that integrate ESG principles into their organization and digital communication tools contribute to the development of sustainable tourism and cultural practices. It is shown that the formation of territorial branding through large-scale art events supports the development of urban infrastructure, attracts investment to the regional budget, and strengthens local cultural and creative communities. Key mechanisms of the impact of events on the city brand have been identified, including the creation of an emotional response among visitors, the formation of media space, the identification of unique cultural features, and the increase in the territory’s recognition in the domestic and international tourist markets. Conclusions. It has been established that an integrative approach to organizing dance festivals is an effective tool for increasing cities’ competitiveness and shaping their positive image. The practical significance of the work lies in determining the directions for the strategic use of large-scale dance events within the territorial branding system, as well as in laying the groundwork for methodological tools to assess the intangible effects of cultural events and plan complex tourist products.